FAKTOR PENGHAMBAT DALAM PENYELESAIAN TUGAS BESAR MAHASISWA PADA MATA KULIAH GAMBAR PERENCANAAN - 508-514 , Foni Rusnanda (Universitas Negeri Padang, 2014)
Abstract The background of this research is the lack of interest and motivation to complete the final assignment of Planning Drawings course so as the learning outcomes is below expectation. This study was conducted to determine factors that become an obstacle for students in the Department of Civil Engineering to complete the final assignment of Planning Drawings course. The type of this research is a descriptive study. The population of the study are students of Department of Civil Engineering who took Planning Drawings course in semester July-December 2012. This study used proportional random sampling, data collection was done by using questionnaire that were distributed to the respondents. The results of the data analysis showed that the factors that become an obstacle in completing the final assignment of Planning Drawing course consist of interest, motivation and learning facilities. Percentages for each factor are: interest at 15.98%, motivation at 17:06% and learning facilities at 17:24%. The total percentage of those three factors is 50.28%. Keywords: hindering factor, final assignment, Planning Drawings course.